Effect of heating rate on biomass liquefaction: Differences between subcritical water and supercritical ethanol - Brand, Steffen; Hardi, Flabianus; Kim, Jaehoon; Suh, Dong Jin (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
This study investigates the influence of heating and cooling rate on liquefaction of lignocellulosic biomass in subH(2)O (subcritical water) or in scEtOH (supercritical ethanol), in dependency of final reaction temperatures (250-350 degrees C) and residence times (1-40 min). The heating rate has been identified as a crucial parameter in the subH(2)O-based liquefaction, whereas it has marginal influence in the scEtOH-based liquefaction. Detailed characterization of gas, liquid and solid products enables to identify the individual reaction steps, which results in a new insight into the reaction mechanisms, depending on the liquefaction solvents and conditions. Similar to fast pyrolysis, hydrothermal liquefaction consists of beneficial primary reactions (pyrolytic & hydrolytic degradation) and non-beneficial secondary reactions i.e. recombination and secondary cracking. In scEtOH, biomass was decomposed by pyrolysis and alcoholysis at relatively high reaction temperatures while the recombination of reaction intermediates are retarded by the unique reactions of scEtOH such as hydrogen donation and hydroxylalkylation. Crown Copyright (C) 2014 Published by Elsevier Ltd. All rights reserved.
Keywords: HYDROTHERMAL LIQUEFACTION; BIO-OIL; CONVERSION; LIGNIN; WOOD; DEGRADATION; CELLULOSE; SLUDGE; WASTE